2012
DOI: 10.1017/s0305000912000499
|View full text |Cite
|
Sign up to set email alerts
|

Plural noun inflection in Kuwaiti Arabic-speaking children with and without Specific Language Impairment

Abstract: This study examined the production of three types of noun plural inflections, feminine sound plural (FSP), masculine sound plural (MSP), and broken plural (BP) in Kuwaiti Arabic-speaking children with and without language impairment. A total of thirty-six Kuwaiti participants - twelve adults, twelve children with specific language impairment (SLI), and twelve typically developing age-matched controls (TD) were presented with twenty-seven pictured stimuli of real and nonsense words. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
16
3
Order By: Relevance
“…This study further revealed that the acquisition of the Welsh plural system is particularly problematic for children with SLI, who differed significantly from their TD peers. This is on a par with the findings in languages with equally complex plural systems (Arabic or Hebrew) (Abdalla et al 2013), but differs from the studies in Icelandic (Thordardottir 2008) and Hungarian (Lukács et al 2010), where mo-SLI children were reported to have less pronounced problems with plural morphology, if at all (Thordardottir 2016). The differences may be due to at least two reasons.…”
Section: Plural Formation In Welsh-speaking Childrencontrasting
confidence: 75%
See 2 more Smart Citations
“…This study further revealed that the acquisition of the Welsh plural system is particularly problematic for children with SLI, who differed significantly from their TD peers. This is on a par with the findings in languages with equally complex plural systems (Arabic or Hebrew) (Abdalla et al 2013), but differs from the studies in Icelandic (Thordardottir 2008) and Hungarian (Lukács et al 2010), where mo-SLI children were reported to have less pronounced problems with plural morphology, if at all (Thordardottir 2016). The differences may be due to at least two reasons.…”
Section: Plural Formation In Welsh-speaking Childrencontrasting
confidence: 75%
“…This finding is less surprising if one considers that plural formation in Semitic languages is more complex than in Germanic languages, and certain plural formation rules are late acquired even by TD speaking Semitic languages (Schiff et al 2011, Ravid andSchiff 2009). These cross-linguistic studies show that children with SLI are less likely to master fully plural formation rules that involve the application of multiple processes (e.g., suffixation plus internal vowel change) compared with their TD peers, less likely to use the right allomorph in specific contexts or over-regularize and, when they do, they overuse the most frequent suffix (Kauschke et al 2011, Abdalla et al 2013.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Research on SLI in Arabic is rather limited (however, see Abdalla and Crago, 2008 ; Aljenaie, 2010 ; Abdalla et al, 2013 ; Fahim, 2017 ; Mahfoudhi and Abdalla, 2017 ; Qasem and Sircar, 2017 ; Shaalan, 2017 ) and it has not yet addressed the role of diglossia in impaired language development. The current study is one step in this direction.…”
Section: Introductionmentioning
confidence: 99%
“…As BP does not follow linear formation rules, it can only be acquired through lexicalisation and learning. It is therefore expected to be mastered after SP (Abdalla, Aljenaie, & Mahfoudhi, 2012 ).…”
Section: Number In Jordanian Arabicmentioning
confidence: 99%